To constitute teacher of Infantile Education - roads and descaminhos - Nilva Bonetti (Universidade Federal de Santa Catarina, 2008)
It is approached in this text the path in the construction of the identity and autonomy in doing educational of two teachers of Infantile Education. Through the autobiographical report Rita and Luiza speak about the choice of the course of Teaching of 2nd Degree from 1st to 4th series, with qualification for Infantile Education, and of your career as teachers. The autobiographical report embraces three phases: the choice of the course, outstanding facts during the course and the contents of the formation, addressed to the Infantile Education. He/she brings the memories of the beginning of the career to the domain of the docência in the first childhood. They stand out the contributions of the formation in medium level and as the knowledge they went being built in the context of the institutions.